Hydrochemical and geophysical characterization of a submerged groundwater discharge in Quintana Roo, Mexico - Cejudo, Eduardo; Acosta-González, Gilberto; Ortega-Camacho, Daniela; Perera-Burgos, Jorge Adrián; Leal-Bautista, Rosa María (Ecosistemas y Recursos Agropecuarios, 2022)
Groundwater discharges (GD) provide information for understanding the local hydrogeology of a region. This study comprehensively describes a GD in the coast of Quintana Roo, quantifying the volumetric discharge and describing the hydrochemistry and geophysics of the site in order to contribute to the knowledge of the coastal karst aquifer in Quintana Roo. The GD described is an oval opening with an approximate area of 0.0507 m2 where major elements, silicates, metals and stable isotopes of water (δ2H and δ18O) were quantified monthly. With the latter data, the contribution of precipitation in the instantaneous discharge was calculated. Also, electrical resistivity tomographies were completed to identify saturated and flow areas. Alkalinity, silicates, sodium and chlorides decrease, and the redox potential increases with the pluvial precipitation, which suggest recharge. The contribution of seawater is greater when volumetric flow is low; as such, the water is of the type sodium-potassium chloride. Groundwater is the greatest contribution, whereas seawater represents between 2 and 16% of the volumetric flow. The contribution of precipitation is between 1% and 15% and is not immediately observed in the GD. The geophysics suggest a free freshwater lens of approximately 2.5 m thick with some recharge zones, as well as small conduction channels in which groundwater flows. Our results capture local and regional aquifer recharge events.